Identification and Antibacterial Activity Test of Lactic Acid Bacteria Isolated from Fermented Shrimp (Cincalok) Against Vibrio parahaemolyticus and Listeria monocytogenes - Gani Samboja, Laurentius Dimas; Purwijantiningsih, Ekawati; Yuda, Pramana (University of Brawijaya, 2019)
Indonesia is a maritime country which has richness of sea products like fish, shrimp, squid, crab, and oyster. Nevertheless, all of those sea products can easily be contaminated by foodborne disease pathogenic bacterias such as Vibrio parahaemolyticus and Listeria monocytogenes. Those two pathogenic bacterias can cause serious illnesses in gastrointestinal tract such as diarhea, vomiting, and stomach cramp. The contamination of pathogenic bacteria can be prevented by lactic acid bacteria (LAB) metabolite compounds such as bacteriocin, organic acid, hydrogen peroxide, and diacetyl. Lactic acid bacteria was isolated from Indonesian traditional fermented shrimp called cincalok. The aim of this research is to do moleculary identify LAB isolates and antibacterial activity test in order to determine the species of LAB and to know the ability of LAB against pathogenic bacteria. Lactic acid bacteria from cincalok was identified by amplifying gen 16S rRNA through PCR colony method using primer LABFw and primer R16SRDNA-1492bac. Lactic acid bacteria from cincalok identified as Enterococcus sp. FTBUAJY01, Enterococcus sp. FTBUAJY02, Enterococcus sp. FTBUAJY03, Enterococcus durans strain FTBUAJY01, dan Enterococcus durans strain FTBUAJY02. Antibacterial activity test was conducted by agar well difusion method. It showed that the greatest inhibition ability of LAB from cincalok showed by Enterococcus sp. FTBUAJY02 against V. parahaemolyticus (0,529 Â± 0,082 cm2) and Enterococcus durans strain FTBUAJY02 against L. monocytogenes (0,655 Â± 0,090 cm2).